Importance of Flaxseed and its Components in the Management of Hypertension - Prasad, Kailash (International Journal of Angiology, 2019)
This review paper describes the effects of flaxseed and its components (flax oil, secoisolariciresinol diglucoside [SDG], flax lignan complex [FLC], and flaxseed protein hydrolysate [FPH]) on blood pressure (BP) in Sprague Dawley rats (SDR), spontaneously hypertensive rats (SHR), and humans. Flaxseed, flax oil, and FLC had variable effects on BP in humans, while SDG and FPH significantly reduced the BP in SDR and SHR. The effect of SDG was dose-dependent and long lasting. The lowering of BP is mediated through inhibition of soluble epoxide by α-linolenic acid in flax oil, stimulation of guanylate cyclase and inhibition of angiotensin converting enzyme (ACE) by SDG, and inhibition of renin and ACE activity by FPH. Flaxseed, flax oil, and FLC have variable effects on BP (none, slight, and significant). They are effective in lowering BP in individuals with hypertension and metabolic syndrome but ineffective in healthy individuals' ineffectiveness of flaxseed and its compounds in lowering BP may be due to their low doses, long interval of dosing, short duration of consumption, and patient status. In conclusion, the data at present suggest that flaxseed, flax oil, and FLC cannot serve as therapeutic agents for the treatment of hypertension. However, they can be used as an adjunct in the treatment of hypertension. A clinical trial should be conducted of these agents with higher doses which would be given twice daily for long duration. Pure SDG and FPS may serve as therapeutic agents for the treatment of hypertension but they have not been tried in humans.
Keywords: flaxseed; flax oil; secoisolariciresinol diglucoside (SDG); flax lignan complex; flaxseed protein hydrolysate; blood pressure; hypertension; inhibition of soluble epoxide hydrolase by α-linolenic acid; inhibition of renin; ACE activity by SDG and protein hydrolysate; stimulation of guanylate cyclase by SDG